1960
DOI: 10.1172/jci104127
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Estrogens Upon the Peripheral Metabolism of Thyroxine *†

Abstract: In plasma, thyroxine is avidly bound to specific proteins present in low concentration, particularly the so-called thyroxine-binding globulin (TBG) and thyroxine-binding pre-albumin (TBPA) (1-4). Several observations indicate that such protein-hormone interactions are of physiological importance. In vitro, the ability of cellular systems to accumulate thyroxine from suspending media is conditioned by the thyroxine-binding potency of the proteins within the media (5, 6). In addition, the volume of distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
3

Year Published

1961
1961
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(36 citation statements)
references
References 37 publications
3
30
0
3
Order By: Relevance
“…As a consequence, the total concentration of hormone in the peripheral pool would decrease until a new steady state is reached when total hormonal disposal once again equals hormonal supply. Presumably, this would occur when the total disposal of hormone has returned 7 In our studies, these compounds were well tolerated by the patients and did not change the state of hydration, as judged from serial measurements of the hematocrit. In three instances, mild dyspepsia occurred, but this was readily relieved by antacids.…”
Section: In Vivo Studiesmentioning
confidence: 60%
See 1 more Smart Citation
“…As a consequence, the total concentration of hormone in the peripheral pool would decrease until a new steady state is reached when total hormonal disposal once again equals hormonal supply. Presumably, this would occur when the total disposal of hormone has returned 7 In our studies, these compounds were well tolerated by the patients and did not change the state of hydration, as judged from serial measurements of the hematocrit. In three instances, mild dyspepsia occurred, but this was readily relieved by antacids.…”
Section: In Vivo Studiesmentioning
confidence: 60%
“…This acceptance is based on studies demonstrating a consistent relationship between changes in the T4-binding activity of TBG, as assessed by electrophoresis in vitro and changes in the concentration and fractional turnover of T4 in vivo (6)(7)(8). From these observations, the conclusion has been drawn that TBG regulates the peripheral metabolism of T4 by limiting the concentration of unbound hormone.…”
mentioning
confidence: 99%
“…Transferrin is a β 1 globulin which transports iron in the blood. This may be a consequence of increased estrogens during pregnancy, stimulating the rise in serum binding capacities, not only of iron, but also other hormones like thyroxine and corticosteroids (Dowling et al, 1960). It has also been suggested that raised serum transferrin levels may result in increased iron absorption (Fletcher et al, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Though evidence is still fragmentary, there is general agreement that thyroid-hormone-plasma-protein interactions may control the action of the thyroid hormone by determining the level of its 'free' diffusible form in the circulation and hence its transfer to the peripheral tissues (Robbins & Rall, 1957, 1960Pitt-Rivers & Tata, 1959;Dowling, Freinkel & Ingbar, 1960). The concentration of free diffusible thyroxine in the blood would therefore play a major role in the thyroid-pituitary homoeostatic 12 G. MORREALE DE ESCOBAR AND F. ESCOBAR DEL REY mechanism, a system which is believed to be regulated so as to maintain a normal intracellular concentration and metabolism of the thyroid hormone.…”
Section: Discussionmentioning
confidence: 99%